2016
DOI: 10.1523/eneuro.0005-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Visuomotor Learning Generalizes Around the Intended Movement

Abstract: Human motor learning is useful if it generalizes beyond the trained task. Here, we introduce a new idea about how human visuomotor learning generalizes. We show that learned reaching movements generalize around where a person intends to move (i.e., aiming direction) as opposed to where they actually move. We used a visual rotation paradigm that allowed us to disentangle whether generalization is centered on where people aim to move, where they actually move, or where visual feedback indicates they moved. Parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
128
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(141 citation statements)
references
References 32 publications
11
128
2
Order By: Relevance
“…However, this interpretation stands in contrast to a recent series of findings demonstrating that explicitly accessible re-aiming processes constitute the majority of learning (Heuer and Hegele, 2008; Hegele and Heuer, 2010; Taylor et al, 2014; Bond and Taylor, 2015; McDougle et al, 2015; Brudner et al, 2016; Day et al, 2016; Poh et al, 2016). We previously found that explicit re-aiming composed the flexible component of performance across a range of rotation magnitudes while implicit recalibration exhibited a stereotyped response (Bond and Taylor, 2015).…”
Section: Introductioncontrasting
confidence: 86%
“…However, this interpretation stands in contrast to a recent series of findings demonstrating that explicitly accessible re-aiming processes constitute the majority of learning (Heuer and Hegele, 2008; Hegele and Heuer, 2010; Taylor et al, 2014; Bond and Taylor, 2015; McDougle et al, 2015; Brudner et al, 2016; Day et al, 2016; Poh et al, 2016). We previously found that explicit re-aiming composed the flexible component of performance across a range of rotation magnitudes while implicit recalibration exhibited a stereotyped response (Bond and Taylor, 2015).…”
Section: Introductioncontrasting
confidence: 86%
“…First, by using a dynamic perturbation alone our study is the first to show that simply having different motor plans, without the confounding effect of dissociating the visual and physical location of the hand, allows opposing perturbations to be learned. Second, studies of visuomotor learning have not separated the concept of a plan from desired state (as noted in Day et al., 2016). Studies such as (Hirashima and Nozaki, 2012) show that subjects can map different desired states (i.e., left and right targets) to different force fields.…”
Section: Discussionmentioning
confidence: 99%
“…1D, [35]). This non-monotonicity, together with evidence using various other methods, has made clear that strategy use and implicit recalibration constitute dissociable and relatively independent learning processes, with their dynamic integration resulting in the observed task performance [24,3445]. …”
Section: Using Multiple Learning Processes In Response To Sensorimotomentioning
confidence: 99%
“…However, it doesn't address how or whether people develop and modify strategies in a more spontaneous manner; that is, when the experimenter does not intervene and provide explicit instructions. To address this issue, we developed a task that provides a trial-by-trial measure of the contributions of explicit aiming and implicit recalibration [24,3739,45]. To assay strategic aiming, participants verbally report their aim direction prior to each reach, providing these reports both before the perturbation and over the course of learning (Figs.…”
Section: Using Multiple Learning Processes In Response To Sensorimotomentioning
confidence: 99%
See 1 more Smart Citation